2015
DOI: 10.4238/2015.january.26.13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the cytotoxic, genotoxic, and mutagenic potential of Acrocomia aculeata in rats

Abstract: ABSTRACT. Acrocomia aculeata (Jacq.) Lodd. ex Mart. is a plant species commonly used as a foodstuff and also for treating diseases, since it contains high concentrations of antioxidant compounds and monounsaturated fatty acids. Considering its ethnopharmacological relevance, the aim of the present study was to assess the cytotoxic, genotoxic, and mutagenic effects of an oil extracted from the pulp of A. aculeata (OPAC) in rats. In addition, a chromatographic characterization of the fatty acids present in OPAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
2
7
0
2
Order By: Relevance
“…Previous findings from our group indicated that OPAC did not exhibit cytotoxic, genotoxic or mutagenic effects in rats (Traesel et al, 2014), which corroborates with the results of the present study. These results demonstrate the absence of acute and subacute toxicity as a consequence of the oral treatment with A. aculeata oil, suggesting that their oral LD50 is higher than 2000 mg/kg.…”
Section: Resultssupporting
confidence: 96%
See 1 more Smart Citation
“…Previous findings from our group indicated that OPAC did not exhibit cytotoxic, genotoxic or mutagenic effects in rats (Traesel et al, 2014), which corroborates with the results of the present study. These results demonstrate the absence of acute and subacute toxicity as a consequence of the oral treatment with A. aculeata oil, suggesting that their oral LD50 is higher than 2000 mg/kg.…”
Section: Resultssupporting
confidence: 96%
“…Our research group has determined the chemical composition of fatty acid of methyl monoesters of the oil obtained from the pulp of A. aculeata (OPAC) through gas chromatography (GC) using methods of mass spectrometry detector (MS) and flame ionization detector (FI) (Traesel et al, 2014). The results are expressed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that the median lethal dose (LD 50 ) was over 2000 mg/kg and that doses of 150-1000 mg/kg did not alter hematologic, biochemical, or histologic parameters. The lack of toxicity was also reported by Traesel et al (2015). This study established the LD 50 with doses above 2000 mg/kg and found a lack of genotoxicity and mutagenicity for doses of 125-2000 mg/kg.…”
Section: Discussionmentioning
confidence: 69%
“…The list of tested plants includes Acrocomia aculeata, a plant native to South and Central America with demonstrated medicinal (Traesel et al, 2014(Traesel et al, , 2015 and nutraceutical (Lescano et al, 2015) properties.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, no oxidative stress‐mediated cytotoxic or genotoxic effects were observed in NIH3T3 fibroblasts after rapeseed oil (63% oleic acid content) exposure (Lewinska et al ). And treatment of Wistar rats with oil extracted from the pulp of Acrocomia aculeata (71% oleic acid content) did not produce cytotoxic, genotoxic, or mutagenic effects (evaluated by comet assay and MN test) (Traesel et al ). Complementarily, oleic acid has been reported to be an effective antimutagenic agent, preventing the mutagenicity of benzo(a)pyrene present in air‐borne particulates (Iwado et al ).…”
Section: Discussionmentioning
confidence: 99%